Electronic palliative care co-ordination systems improve information provided to out of hours teams. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Smith, Clare; Hough, Libby; Whitmore, David; Cheung, ChiChi; Riley, Julia
Abstract : The UK Department of Health (DOH) End-of-life care strategy advocates Electronic Palliative Care Coordination Systems (EPCCS) to improve communication across providers in acute and community sectors 24 h a day. The Royal Marsden NHS Foundation Trust was an EPCCS pilot site. This audit compares the information available to the London Ambulance Service (LAS) on the EPCCS to the information previously provided by a faxed paper form. Aim: To determine if the EPCCS improved the quality of the information shared. Methods: Faxed Palliative Care Handover Forms (PCHF) held at LAS at one time point prior to EPPCS were compared to all EPPCS entries 10 months after implementation. Results: When comparing the PCHF to the EPPCS, the average age of patients (78 years) remained the same. The proportion of patients with a diagnosis other than cancer increased (33% PCHF vs 48% EPPCS) and the number of GPs completing information increased using EPCCS (29% PCHF vs 39%). Consent improved with consent evident on 49% of PCHFs and mandatory (100%) on EPCCS. The EPCCS was designed with mandatory fields leading to improvements in data completion of the following; 'Has the patient been prescribed strong opioids?' 85.1% (n=135) PCHF vs 100% (n=145) EPCCS 'Has resuscitation been discussed with the patient?' 64.9% (n=100) PCHF vs 100% (n=145) EPCCS, 'Has resuscitation been discussed with the carer?' 66.9% (n=103) PCHF versus 100% (n=145) EPCCS. EPCCS also improved completeness of non-mandatory fields; 'Is there a signed Do Not Attempt Resuscitate form in the house?' (91% vs 77.9%), 'Are there emergency drugs left in the home?' (95.2% vs 50%), 'Is death anticipated?' (96.6% vs 85.1%). Conclusion: EPCCS does improve data quality covering aspects of care including resuscitation and the end of life phase. This provides support for EPCCS on a wider scale.